- Legal Politic As Counter An Asymmetrical Warfare In The 5 & 6th Generation War: - - M. Rezza Nuril Aulia; Mhd Halkis; Fauzia Gustarina Cempaka Timur (CV. AFDIFAL MAJU BERKAH, 2024)
Legal politics as a defense system against asymmetric war is very important. War today is no longer conventional but has entered the 5th and 6th generations in an asymmetric and hybrid manner. This research uses an explanatory qualitative method. The analysis technique uses the soft system method (SSM) to provide structured, comprehensive and sharp analysis. In general, this research will discuss legal political alignments in Indonesia, urgency, mechanisms, and the model/concept of Counter Asymmetric War. Specifically, this research discusses political law as a defense system against asymmetric war in the 5th and 6th generation war era which is considered less comprehensive and non-specific. Then, this research determines 4 ideal criteria for Political Law as a defense system against asymmetric war in the 5th and 6th generation war era, including: defense budget, regulatory effectiveness, modernization of technology & defense equipment, and national defense education. These ideal criteria are used to analyze legal politics as a defense system against asymmetric war. The results of the analysis show that the criteria for political law as a defense system against asymmetric war do not comprehensively cover these 4 ideal criteria. As a recommendation, these 4 ideal criteria can be a refinement of the political legal criteria as a defense system against asymmetric war. So that legal political policy as a defense system against asymmetric war can realize the stability of Indonesia's national defense and security.